Trends of changes in structure of physical fitness among young athletes - Karpowicz, K.; Janowski, J.; Karpowicz, M.; Strzelczyk, R. (Trends in Sport Sciences, 2016)
Introduction: Training of children and young people is one of the most important stages and subsystems in coaching and determines future achievements of adult athletes. Level of physical fitness determines effectiveness of coaching and development of technical skills, influences the effectiveness of tactical actions and has an impact on current psychical disposition of a person. Aim of Study: The research presented herein focused on establishing trends in the changes of young fencers` motor effects (their structure and level) in the period of 2006-2013 with reference to tasks aimed to comprehensively shape functional, fitness and technical foundations that take account of requirements set by a desired specialisation and regarded as typical for an oriented stage of sport training. Material and Methods: The study was based on the findings of research carried out 2006-2013 among young fencers - members of the Junior Team of the Greater Poland region (KWJ). The analysis involved a total of 200 boys aged 15 to 16. Measurements - designed to determine the level and structure of the fencers` motor effects - were conducted by means of the International Physical Fitness Test. The test was also to assess basic somatic parameters, such as body height and weight, and to calculate the BMI. Results: The research found out that the general physical fitness of young fencers established on the basis of the International Physical Fitness Test - decreases in subsequent age groups. It may be a consequence of a regressive trend in intergenerational motor changes generally observed in the population, or relate to a change in height-and-weight proportions leading to an increase in body corpulence. Conclusions: A significant drop in strength related to overcoming one`s body resistance is most likely an outcome of the above-mentioned changes in the body structure. Therefore, as it appears, this fact should not be regarded as confirming a view that the so-called strong types of physical fitness are now more seldom among young people. A rise in endurance abilities in the period under research is a positive phenomenon from the point of view of fencing requirements, but also or even mainly - in the context of reversing the negative trend as regards lower general fitness of the young generation.